2016
DOI: 10.1183/13993003.00893-2016
|View full text |Cite
|
Sign up to set email alerts
|

Progression to tuberculosis disease increases with multiple exposures

Abstract: During a single year, a Canadian village had 34 individuals with microbiologically confirmed tuberculosis (TB) among 169 people with a new infection (20%). A contact investigation revealed multiple exposures for each person. We investigated whether the intensity of exposure might contribute to this extraordinary risk of disease.We carried out a case-control study using a public health database. Among those with a new infection, 34 had culture-confirmed TB (cases) and 118 did not progress to disease (controls).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
7
25
0
Order By: Relevance
“…The increase in disease risk with increasing exposures found in (2) could be explained by an independent effect of each infection on risk of progression (reinfection model), or by a high risk of progression once the cumulative number of exposures exceeds a threshold value (threshold model). Previous work has shown that the effect of increasing disease risk with increasing exposures persists after adjustment for a number of covariates (2). Here we found that the threshold model conferred an improved fit relative to the increasing-risk model, providing evidence for a threshold effect.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The increase in disease risk with increasing exposures found in (2) could be explained by an independent effect of each infection on risk of progression (reinfection model), or by a high risk of progression once the cumulative number of exposures exceeds a threshold value (threshold model). Previous work has shown that the effect of increasing disease risk with increasing exposures persists after adjustment for a number of covariates (2). Here we found that the threshold model conferred an improved fit relative to the increasing-risk model, providing evidence for a threshold effect.…”
Section: Discussionsupporting
confidence: 61%
“…Based on previously published TB models (8), we developed binomial risk models for TB infection during the first year after infection and fit these models to data from a TB contact investigation in a largely Inuit (>90%) village of 933 people. Study design and data collection are described in detail elsewhere (2,13). Data consisted of the number of TB exposures for 149 recently-infected individuals, and whether these individuals developed active TB disease within the following year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This outbreak, which has been previously described, 4,7 comprised 50 microbiologically-confirmed cases of TB who were diagnosed in a single Inuit community between 2011-2012 - a rate of 5,359/100,000 for that year. Genomic epidemiology analyses using sequencing depths of ∼50x that are standard in such work, identified multiple clusters of transmission in this outbreak, 4 however, there was insufficient genetic variation detected to infer precise person-to-person transmission events within these subgroups.…”
Section: Introductionmentioning
confidence: 97%